MROS: A framework for robot self-adaptation - Silva, Gustavo Rezende; Garcia, Nadia Hammoudeh; Bozhinoski, Darko; Deshpande, Harshavardhan; Oviedo, Mario Garzon; Wasowski, Andrzej; Montero, Mariano Ramirez; Corbato, Carlos Hernandez (Proceedings (IEEE/ACM International Conference on Software Engineering Companion. Online), 2023)
Self-adaptation can be used in robotics to increase system robust- ness and reliability. This work describes the Metacontrol method for self-adaptation in robotics. Particularly, it details how the MROS (Metacontrol for ROS Systems) framework implements and pack- ages Metacontrol, and it demonstrate how MROS can be applied in a navigation scenario where a mobile robot navigates in a factory floor. Video: https://www.youtube.com/watchvISe9aMskJuE